Kritik Asas Pengayoman Penataan Ruang Terhadap Ketiadaan Norma Utilitas Telekomunikasi dalam Pasal 35 Sampai Pasal 37 Undang-Undang Nomor 26 Tahun 2007 - Alexander, Donny Bonar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to explain the regulation of space utilization and control in Articles 35, 36, and 37 of Law Number 26 of 2007 concerning Spatial Planning, as well as to examine a critique of the Principle of Protective Governance (Asas Pengayoman) regarding these regulations. This research employs a qualitative method with a library research design. The author conducted an in-depth analysis of existing legal norms and relevant literature to dissect issues related to digital infrastructure utilities. The results indicate that, first, Articles 35, 36, and 37 of Law No. 26/2007 serve as procedural foundations stipulating that space utilization must be based on work programs and budgets, synchronized with regional spatial plans (RTRW), and supervised through zoning and licensing instruments. Second, these articles are found not to be fully aligned with the Principle of Protective Governance, as their normative formulations tend to be “bureaucracy-centric,” emphasizing administrative aspects only and failing to ensure the protection and physical safety of the public from the real impacts of chaotic utility infrastructure in public spaces..